Spin-Orbit Coupling Through Inelastic Scattering on Intrasubband Spin Density Excitation (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the spin-orbit coupling via inelastic scattering on the intrasubband  spin density excitation. Resonant in elastic scattering was applied to the probe of the  anisotropic spin splitting of two dimensional hole systems in p-modulation doped  gallium arsenide quantum wells. Intrasubband spin density excitations on a sample  was used where evidence of the persistent spin helix was shown by direct spatial  mapping. We found approximately equal strengths of Rashba and Dresselhaus spin orbit coupling and anisotropy maximal. The spin splitting for in plane spin was also  found maximal and in the perpendicular [110] direction was smaller. The spin  splitting of in plane of about 0.18 meV and in the perpendicular in plane direction  was found to be smaller than 0.05 meV. We have theoretically studied that only spin  flip transitions between the spin orbit split conduction band subbands contributed  significantly to the intrasubband spin-density excitation in quasi-backscattering  geometry. The obtained results were found in good agreement with previously  obtained results.